Codonmyces lecanorae Calat. & Etayo is a new species of lichenicolous fungi for Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
An information about Codonmyces lecanorae Calat. & Etayo – new species of lichenicolous fungi from Ukraine is given. The species grows on thallus and apothecia of Protoparmeliopsis muralis (Schreb.) M. Choisy and is characterized by conidiogenous cells which have 1–4 conspicuous annellations and 1–septate conidia. The paper describes morphologic peculiarities, location, ecology and distribution of this species.
Keywords: Codonmyces, lichenicolous fungi, southern Ukraine.